2022
DOI: 10.1113/jp283895
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of PKD2 channel function by TACAN

Abstract: Autosomal dominant polycystic kidney disease is caused by mutations in the membrane receptor PKD1 or the cation channel PKD2. TACAN (also termed TMEM120A), recently reported as an ion channel in neurons for mechanosensing and pain sensing, is also distributed in diverse non‐neuronal tissues, such as kidney, heart and intestine, suggesting its involvement in other functions. In this study, we found that TACAN is in a complex with PKD2 in native renal cell lines. Using the two‐electrode voltage clamp in Xenopus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(37 citation statements)
references
References 46 publications
0
37
0
Order By: Relevance
“…PKD2 is a non-selective ion channel that is permeable to divalent cations and monovalent ions (Brill & Ehrlich, 2020;Chebib et al, 2015). Using extracellular solutions containing 100 mM Na + , Li + , K + , or non-permeant N-methyl-d-glucamine, Liu et al (2022) investigated whether TACAN affects the ion selectivity of F604P. The finding suggested that despite TACAN inhibiting the channel activity of F604P, it does not affect the ion selectivity of F604P.…”
Section: The Mechanism Of Pkd2 Channel Regulation By Tacanmentioning
confidence: 99%
See 4 more Smart Citations
“…PKD2 is a non-selective ion channel that is permeable to divalent cations and monovalent ions (Brill & Ehrlich, 2020;Chebib et al, 2015). Using extracellular solutions containing 100 mM Na + , Li + , K + , or non-permeant N-methyl-d-glucamine, Liu et al (2022) investigated whether TACAN affects the ion selectivity of F604P. The finding suggested that despite TACAN inhibiting the channel activity of F604P, it does not affect the ion selectivity of F604P.…”
Section: The Mechanism Of Pkd2 Channel Regulation By Tacanmentioning
confidence: 99%
“…In terms of mechanism, the regulation of PKD2 channel function was previously reported to involve multiple factors such as the localization of PKD2, the interaction with other channels, and post-translational modification (Brill & Ehrlich, 2020;Chebib et al, 2015). Liu et al (2022) showed that TACAN-PKD2 physical association is critical in the functional regulation of PKD2 by TACAN. TACAN interacts with PKD2 in the cilia and plasma membrane, supported by PKD2-TACAN colocalization with the cilia marker Arl13b.…”
Section: The Mechanism Of Pkd2 Channel Regulation By Tacanmentioning
confidence: 99%
See 3 more Smart Citations